Pengembangan Model Latihan Passing Sepakbola Berbasis Sasaran Teman - Pujianto, Dian; Sutisyana , Ari; Arwin, Arwin; Nopiyanto, Yahya Eko (Journal Coaching Education Sports, 2020)
Abstract The number of weaknesses in football matches, especially weaknesses in terms of passing a ball, is one of the keys to the failure of a team in a match. This research aims to develop a form of passing football practice. This study uses a development research approach with a sample of UNIB PJKR students. The data analysis technique used is the t-test with calculations through SPSS version 16. The t-test results showed that the coefficient of significance was 0,000, this coefficient was compared with the significance level of 0.05. Based on the comparison it turns out that the coefficient of significance is smaller than the significance level of 0.05, so it can be concluded that the passing training program has an effect on the ability of passing students. Based on the results of the hypothesis testing soccer passing training model has a significant influence on the ability of passing from students, so it can be concluded that this passing training model can be used for students or students who are just practicing football passing.. Keywords: Development, Model, Passing Abstrak Banyaknya kelemahan dalam pertandingan sepakbola terutama kelemahan dalam hal mengoper bola menjadi salah satu kunci kegegalan suatu tim dalam bertanding. Penelitian ini bertujuan mengembangkan bentuk latihan passing sepakbola. Penelitian ini menggunakan pendekatan penelitian pengembangan dengan sampel mahasiswa PJKR UNIB. Teknik analisis data yang digunakan menggunakan uj-t dengan perhitungan melalui SPSS versi 16. Hasil uji-t menunjukkan bahwa koefisien signifikasi sebesar 0,000, koefisien ini dibandingkan dengan taraf signifikasi 0,05. Berdasarkan perbandingan ternyata koefisien signifikasi hitung lebih kecil dari taraf signifikasi 0,05, sehingga dapat disimpulkan program latihan passing memberikan pengaruh terhadap kemampuan passing mahasiswa. Berdasarkan hasil uji hipotesis model latihan passing sepakbola telah memberikan pengaruh yang berarti terhadap kemampuan passing dari mahasiswa, sehingga dapat ditarik kesimpulan bahwa model latihan passing ini dapat digunakan kepada mahasiswa atau pelajar yang baru berlatih passing sepakbola. Kata kunci: Pengembangan, Model, Passing